Inventory of non-volant small mammals in the mixed-land use habitats at Pusat Penyelidikan Pertanian Tun Razak, Jerantut, Pahang - Siti Nur Liyana Roslan; Nor Irdina Anwar; Muhammad Afif Yusof; Hamzah Talibe; Farah Ayuni Farinordin; Nur Amalina Mohd Izam; Nur Athirah Abdullah; Muhammad Farhan Abd Wahab (Penerbit UTM Press, 2025)
The extensive use of land for agriculture has significantly influenced the distribution and diversity of wild species, including small mammals. From 22nd February to 17th March 2023, an inventory was conducted to identify the diversity and bait preferences of non-volant small mammals across three localities which are oil palm, orchard and forest area at Pusat Penyelidikan Pertanian Tun Razak (PPPTR), Jerantut, Pahang. A total of 105 individuals representing three families and six species of the orders Rodentia and Scandentia were trapped and identified. Out of this, four species from 26 individuals were caught in the oil palm area, six species from 36 individuals in the orchard, and five species from 43 individuals in the forest area. Rattus tiomanicus was the most abundant species recorded at PPPTR. The Shannon-Wiener Index was calculated and compared, showing that the forest area (H = 1.391) had a greater diversity value than the oil palm (H = 1.293) and orchard (H = 1.367). Simpson's Diversity Index also revealed that the forest area (0.7258) had a higher index value than the oil palm (0.7012) and orchard (0.6852), indicating that the forest area has better habitat suitability for small mammals. The analysis of bait preferences revealed that non-volant small mammals at PPPTR showed a strong preference for oil palm loose fruit, followed by bananas, likely due to dietary habits and food availability in the area. In conclusion, this inventory provides fundamental data on non-volant small mammal diversity in the mixed-land use habitats at PPPTR and offers valuable insights for small mammals’ conservation and agricultural pest management strategies.